PENINGKATAN KEMAMPUAN MENULIS PUISI MENGGUNAKAN MEDIA GAMBAR SISWA KELAS V SDN III TOAYA - Nurjannah, Nurjannah (BAHASANTODEA, 2016)
The objective of classroom action research was to describe a result of an improvement writing of poetry ability of fifth grade students at SDN No. 3 Toaya after it was applicating the using of learning picture media. The dta observation of the students analyzed by qualitative with using observation paper of activating student and teacher. The result of free poetry writing ability by quantitative using descriptive analysis. Based on the data analysis and explanation of research result, it is obtained the data : class average score in learning writing of poetry at the cycle I achieve 69,76, and at the cycle II achieve 75,2. It was showed there was an improvement of class average score from cycle I to the cycle II was 5,44. From the obtaining of the data, it is can be concluded that the application of picture media can improve writing poetry ability at the fifth grade students at SDN No. 3 Toaya.